Oestrus and fertility after prostaglandin injection in Kedah-Kelantan cattle - Tan, H. S.; Chew, S. T.; Haron, Kassim; Mak, T. K. (1984)
In view of a lack of published information on oestrus synchronization in indigenous beef cattle, the effects of prostaglandin F₂α (PG) on oestrus and fertility in 50 Kedah-Kelantan cows were investigated. In trial I, 30 cows (G1, G2; n = 15) with palpable corpora lutea were given a single PG injection. In G1, insemination was performed after detection of standing oestrus while G2 animals were inseminated at 72 and 96 hr post-treatment. In trial II, 20 animals were given a double injection of PG, 10 days apart, and inseminated at 72 and 96 hr (G3). Eighty percent (12/15) of animals in G1, 100 percent (15/15) in G2 and 100 percent (20/20) in G3 responded to PG treatment, coming into oestrus between days 3 and 6 post-injection. Mean (+ S.D) times to onset of standing oestrus were 86.9 + 17.4 (G1, 83.3 + 29.2 (G2) and 66.5 + 20.4 hr (G3). Individual variations in vulval conformation made interpretation of vulval swelling very subjective and unreliable. Only 11.1% of animals in Trial I and 20% in Trial II exhibited spontaneous vaginal mucus discharge at the induced oestrus. Mean plasma progesterone levels showed a marked decline after PG treatment and standing oestrus coincided well with basal values. Based on progesterone profiles, conception rates were 25% (G1), 33% (G2) and 50% (G3). Conception failure was the primary cause of low pregnancy although embryonic mortality was also detected. Asynchrony of fixed time A.I. and induced oestrus was observe in 10% of animals.